The Death Penalty, Its Pros and Cons, When and Why it Can be Justified (A Field Study for Students of the Faculty of Arts, Al-Ahliyya Amman University) - Al_Shyaab, Khaled Omar Mohammad (Journal of Ecohumanism, 2024)
The aim of this research was to identify the death penalty in terms of its pros and cons, and when and why it can be justified, through a field study on students of the Faculty of Arts at Al-Ahliyya Amman University, using the descriptive approach, and by applying it to a sample of (450) male and female students who were chosen randomly, With the design of a questionnaire to collect information, the research concluded that the positives of the death penalty are attributed to the benefit of males, while the negatives are attributed to the benefit of females. Also, when the death penalty is justified is attributed to the benefit of married people, while why the death penalty is justified is attributed to the benefit of the educational stage.